Alterations in the cardiac proteome of the spontaneously hypertensive rat induced by transgenic expression of CD36 - Manakov, Dmitry; Ujcikova, Hana; Pravenec, Michal; Novotny, Jiri (Journal of proteomics, 2016)
Fatty acid translocase (FAT/CD36) plays an important role in fatty acid uptake by different cell types and may also participate in regulation of calcium homeostasis and eicosanoid production. CD36 deficiency or polymorphisms in the CD36 gene are linked to some physiological irregularities. It is known that the expression of FAT/CD36 is aberrant in the spontaneously hypertensive rat (SHR), one of the most widely studied rat strains in cardiovascular research. In this work, we compared the cardiac proteome of SHR and transgenic SHR-Cd36 rats, who carry a copy of the wild type CD36 gene. Protein expression profiling was based on two-dimensional gel electrophoresis (2DE) coupled to tandem mass spectrometry and label-free LC/MS. These two complementary proteomic approaches allowed us to investigate proteome differences in the left and right heart ventricles of SHR and SHR-Cd36 rats. In total, we identified 26 differently expressed myocardial proteins, out of which 18 were found in the right ventricles and 8 in the left ventricles. Besides that, we determined a great number of proteins uniquely expressed either in the left or right ventricles. These data indicate a large qualitative disparity between the left and right ventricles. Genetic manipulations may affect different proteins in both heart ventricles. Biological significance: This is the first report revealing a relatively broad impact of transgenic expression of CD36 on the heart at the proteome level. Comparison of the protein profiles in both the left and right ventricles revealed differences in several proteins involved especially in energy metabolism. The observed downregulation of the respiratory chain enzymes in transgenic SHR-Cd36 rats may suggest a shift in regulation of energy metabolism due to expression of fatty acid translocase FAT/CD36. This study highlights the important role of cardiac tissue proteomic profiling for mapping of proteins which might be altered by targeted genetic manipulations.
Keywords: proteom; Chromatography, Liquid; 2D gelová elektroforéza; Tandem Mass Spectrometry; Proteomics; Transgenes; krysa rodu Rattus; zvířata; transgeny; Left and right ventricles; proteomika; tandemová hmotnostní spektrometrie; Energy Metabolism; energetický metabolismus; chromatografie kapalinová; potkani inbrední SHR; Heart; Electrophoresis, Gel, Two-Dimensional; CD36 Antigens; Heart Ventricles; Rats; myokard; Proteome; Animals; Myocardium; CD36; SHR; Rats, Inbred SHR; antigeny CD36; srdeční komory